Multiple research approach on the productivity of university students in the coffee shop interior environment - Pascual, Catherine Nicole C.; Faustino, Johanna Victoria Acab (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
Abstract This study explored the coffee shop as an environment for work and productivity. This study was triggered by the apparent migration of students from the library or the home to coffee shops. Specifically, this study investigated the features and characteristics of the coffee shop?s physical and social interior environment which influence the user?s work and productivity. Moreover, it sought to find out if the coffee shop is an ideal environment for studying. A multiple research approach was used to give the study a more holistic perspective. The researcher conducted the study in two phases: a survey and field studies. A survey was conducted to delineate the user?s ideal environment for work and productivity, moreover it extracted data regarding the coffee shop experience of the respondents. Sixty respondents, who were university students who studied in coffee shops, were selected through non-probability purposive sampling. From the results of the survey, top preferred coffee shops near four selected universities emerged. Four coffee shops were selected in total. These coffee shops were then documented and observed. Data acquired from the various research methods were correlated and analyzed. Findings from this study reveal that the coffee shop?s interior environment is able to influence work and productivity by fostering a unique balance of the private and public spheres. Findings also show that respondents see the coffee shop as the mid-place between the home and library. Moreover, the different features and characteristics unique to the interior environment of coffee shops were able to exude relaxation and comfort which the respondents found conducive for informal learning.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Coffee shops -- Philippines; Coffee shops -- Interior decoration -- Psychological aspects